2020
DOI: 10.1093/pubmed/fdaa146
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing treatment outcomes of tuberculosis patients attending health facilities in Galkayo Puntland, Somalia

Abstract: Aim This study evaluated the underlying factors associated with poor tuberculosis (TB) treatment outcomes among patients attending health care facilities in Galkayo, Puntland, Somalia. Methods An institution-based cross-sectional study was conducted between 2016 and 2017 in three selected TB clinics. Data were collected from 400 TB patients, through medical record review and structured questionnaire. Multivariate logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
3
6
1
Order By: Relevance
“…This result is higher than the studies conducted in Ghana (68.46%) 35 , North-Central Nigeria (67.4%) 36 , Somalia (85%) 15 , Wolayta Sodo, Southern Ethiopia (82.5%) 26 , Woldia, Northeast Ethiopia (80.7%) 24 , Adama City, Ethiopia (80.8%) 37 , Asella, Ethiopia (81.7%) 21 , Gambella, Southwest Ethiopia (70.76%) 38 , West Ethiopia (82.5%) 39 , Gedeo Zone, Southern Ethiopia (66.44%) 40 , Addis Abeba (82.7%) 13 , Ethiopian University Hospitals (60.1%) 41 , Dessie and Woldiya Town, Northeast Ethiopia (88.1%) 42 , and Debre Markos, Northwest Ethiopia (59.3%) 43 . Differences in sociodemographic characteristics, cultural practices, and socioeconomic status among these regions may contribute to variations in treatment outcomes.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…This result is higher than the studies conducted in Ghana (68.46%) 35 , North-Central Nigeria (67.4%) 36 , Somalia (85%) 15 , Wolayta Sodo, Southern Ethiopia (82.5%) 26 , Woldia, Northeast Ethiopia (80.7%) 24 , Adama City, Ethiopia (80.8%) 37 , Asella, Ethiopia (81.7%) 21 , Gambella, Southwest Ethiopia (70.76%) 38 , West Ethiopia (82.5%) 39 , Gedeo Zone, Southern Ethiopia (66.44%) 40 , Addis Abeba (82.7%) 13 , Ethiopian University Hospitals (60.1%) 41 , Dessie and Woldiya Town, Northeast Ethiopia (88.1%) 42 , and Debre Markos, Northwest Ethiopia (59.3%) 43 . Differences in sociodemographic characteristics, cultural practices, and socioeconomic status among these regions may contribute to variations in treatment outcomes.…”
Section: Discussioncontrasting
confidence: 60%
“…Factors affecting TB outcomes are crucial indicators of TB control program success. Prompt initiation and adherence to national TB treatment standards are essential for effective therapy 15 . Monitoring the proportion of patients who receive successful treatment is key in evaluating the TB DOT program, particularly for those with TB and HIV co-infections due to potential treatment variables 6 .…”
Section: Introductionmentioning
confidence: 99%
“…26 , 42 , 52 , 57 , 62 , 74 , 82 , 93 , 119 , 123 , 126 , 138 So-called unsuccessful treatment, which combined any outcome other than cure or completion of treatment, was reported in 28 studies. 24 , 49 , 60 , 61 , 65 , 68 , 71 , 73 , 78 , 80 , 85 , 87 , 90 , 91 , 94 , 95 , 104 , 107 , 108 , 114 , 117 , 122 , 123 , 126 , 137 , 140 , 145 , 146 Of these, the risk could not be extracted from four studies, 24 , 49 , 61 , 137 whereas most of the remaining ones reported increased risk, including three studies that included the use of ST products. 91 , 104 , 122 …”
Section: Resultsmentioning
confidence: 99%
“…In another study from Tanzania, diabetes was associated with a fivefold increased risk of mortality (RR = 5.0, 95% CI 2.4–11.0) during the intensive phase of TB treatment [27] . A cross-sectional study from Somalia reported that the odds of poor TB outcomes among patients diagnosed with diabetes was eight-times higher that TB patients without diabetes (OR: 8.02 (1.79–35.86) [28] . Similarly, a case–control study from Egypt reported more than a nine-fold increased risk of treatment failure (RR = 9.32 (2.7–31.69) among patients with TB and diabetes compared to those without diabetes [29] .…”
Section: Discussionmentioning
confidence: 99%